Identificación de la riqueza florística de la quebrada guadalupe de la subcuenca del Rio Illuchi, cantón Latacunga, provincia Cotopaxi, período 2015 - Oña Maigua, Mayra Alexandra (2016)
The present research reflects the current state of the floristic wealth of the Guadalupe ravine, and provides information about the taxonomic characteristics, description and use of the species identified. In the area of study (10 transects) were recorded 76 species, corresponding to 37 families, of which 7 species are endemic and have a status of conservation, according to the International Union for the Conservation of Nature (IUCN), And these are: 4 species vulnerable, 2 species of least concern, and one is near threatened. The same that have uses food, medicine, ornamental, firewood, etc.; as well as there are species that help the conservation, protection and regulation of the environment....